Avaliação ultrassonográfica gástrica em pequenos animais - Silva, Luciana Carandina da [UNESP] (2013)
In small animal clinic, we often faced with diseases that lead to gastric and intestinal changes such as pyometra, pancreatitis, renal failure, presence of gastric or intestinal foreign body, nematode infections and viral diseases. The use of imaging as an aid in the differentiation of these disorders is essential. Ultrasonography has great value in assessing gastric visualization and measurement of the wall and folds, and enable the identification of intraluminal content. In this review was describe the sonographic technique for assessing gastric as well as their normal features and changes found in major diseases affecting small animals.